Ying-Shih Yü, Trade and Expansion in Han China. A Study in the Structure of Sino-Barbarian Economic Relations. University of California Press, Berkeley y Los Angeles, 1967. 251 pp. - Payró, Ana Lía (Estudios de Asia y África, 1971)
-